Rekonstruksi Cantik pada Perempuan (Analisis Semiotika Lirik Lagu Alessia Cara “Scars to Your Beautiful”) - Gunawan, Ana Theresa; Sukendro, Gregorius Genep (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2022)
Music is a kind of communication that is used to convey information to others. Alessia Cara's song Scars to Your Beautiful is one of the songs with significant meaning. The song shows how important it is for every lady to appreciate her own beauty. The purpose of this research is to describe Alessia Cara's song's meaning. In this study, the social reconstruction model was used. People's skepticism about societal change is explained by the model. The song